2017
DOI: 10.1097/qai.0000000000001403
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Risk Behaviors of Men Who Have Sex With Men and Women Compared With Men Who Have Sex With Men—20 US Cities, 2011 and 2014

Abstract: MSMW have distinct sexual risk behaviors from MSMO and may contribute to HIV transmission among women. MSMW could benefit from tailored interventions to reduce HIV risk behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 61 publications
(71 reference statements)
0
11
1
2
Order By: Relevance
“…In addition, we found that MSM who reported a history of STIs were more likely to engage in the co-occurrence of smoking and drug use. Despite no relationship between smoking and HIV status in this study, previous research has demonstrated that risky behaviors and outcomes, such as having multiple male sexual partners, unprotected sexual intercourse, and STIs, are linked to a high prevalence of HIV infection among MSM [22,24]. In the current study, the online sampling methodology may not produce these same results.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In addition, we found that MSM who reported a history of STIs were more likely to engage in the co-occurrence of smoking and drug use. Despite no relationship between smoking and HIV status in this study, previous research has demonstrated that risky behaviors and outcomes, such as having multiple male sexual partners, unprotected sexual intercourse, and STIs, are linked to a high prevalence of HIV infection among MSM [22,24]. In the current study, the online sampling methodology may not produce these same results.…”
Section: Discussioncontrasting
confidence: 60%
“…Additionally, many studies have shown that MSM's cigarette smoking is positively associated with HIV-related behavioral and sexual risks, including usage of alcohol and a variety of traditional and synthetic illicit drugs, such as heroin, marijuana, and methamphetamine [7,20,21], and a greater number of casual sex partners [20]. Meanwhile, sex with casual male partners and unprotected anal sex have been found to be associated with HIV and other sexually transmitted infections (STIs) [22][23][24]. A recent study conducted in the U.S. by the Multicenter AIDS Cohort Study found that smoking at least one pack of cigarettes per day was positively associated with being HIV-seropositive among MSM; furthermore, detectable viral load of HIV was significantly associated with prevalence of smoking among HIV-seropositive MSM [25].…”
Section: Cigarette Smoking and Hiv-related Risksmentioning
confidence: 99%
“…MSM are still vulnerable to HIV infection, as documented by the persistence of high prevalence of infection in this group, despite an overall decline of new infections in the general population [ 21 , 24 ]. Data from the US Center of Disease Control and Prevention (CDC) report that 54% of estimated HIV diagnoses in United States in 2014 are in MSM, even if they represent only the 2% of the population [ 25 ]. A previous Italian study reported an increased risk of HIV seroconversion in younger MSM throughout the study period (1984–2010) [ 26 ]; similar data were confirmed in other European studies with a double risk of HIV in MSM aging 20–29 years from 2003 to 2012 [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regular sex partners referred to those with sexual relationship alone over extended periods, whereas non-regular sex partners were typically one-night-stand partners without extended relationship. For statistical presentation, three types of sex partners were recategorised into two groups using a more common distinction, namely main and casual sex partners [29]. Lovers and regular sex partners were considered as main sex partners, with whom the respondents felt committed or had an extended relationship.…”
Section: Methodsmentioning
confidence: 99%